F Fenomenologi Heidegger dan Epistemic Injustice: Kritik Terhadap Dominasi Artificial Inteligence dalam Struktur Pengetahuan Manusia: Heidegger's Phenomenology and Epistemic Injustice: A Critique of the Dominance of Artificial Intelligence in the Structure of Human Knowledge - Mukmin, Muhammad Andry; Putri, L.G Saraswati (Jurnal Filsafat Indonesia, 2025)
This research examines how Artificial Intelligence influences the structure of human knowledge through the lens of Martin Heidegger’s phenomenology and Miranda Fricker’s theory of Epistemic Injustice. Artificial Intelligence is not merely a technological tool but a part of Gestell that limits the way humans understand reality. This framing contributes to epistemic injustice, particularly in the form of testimonial injustice, when human epistemic authority is replaced by Artificial Intelligence systems, and hermeneutical injustice, when the experiences of certain groups are excluded from knowledge structures due to algorithmic bias. This study emphasizes the need for reflective awareness, the development of transparent Artificial Intelligence regulations, and social participation in technological design to prevent the subordination of humans to knowledge systems framed by Artificial Intelligence.